2012
DOI: 10.1002/emmm.201201703
|View full text |Cite
|
Sign up to set email alerts
|

Acute B lymphoblastic leukaemia‐propagating cells are present at high frequency in diverse lymphoblast populations

Abstract: Leukaemia-propagating cells are more frequent in high-risk acute B lymphoblastic leukaemia than in many malignancies that follow a hierarchical cancer stem cell model. It is unclear whether this characteristic can be more universally applied to patients from non-‘high-risk’ sub-groups and across a broad range of cellular immunophenotypes. Here, we demonstrate in a wide range of primary patient samples and patient samples previously passaged through mice that leukaemia-propagating cells are found in all populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
73
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(82 citation statements)
references
References 63 publications
(115 reference statements)
8
73
1
Order By: Relevance
“…Here, cryopreservation obscured the true frequency of LSCs, which is the highest reported to date for precursor T-ALL, and among the highest cancer-initiating cell frequencies reported for any primary malignancy. Our observations for fresh cell transplants are consistent with the proposal that all blasts, or at least a very high proportion, may have leukaemia-initiating potential in some cases of human ALL (Rehe et al, 2013). Furthermore, given that the patient achieved complete morphological and molecular remission with first line chemotherapy and remains in remission 12 months from diagnosis, they also suggest, at least in this case, that existing chemotherapy regimens in ALL successfully target the great majority of cells with leukaemia-initiating potential.…”
Section: Very High Frequencies Of Leukaemia-initiating Cells In Precusupporting
confidence: 90%
See 2 more Smart Citations
“…Here, cryopreservation obscured the true frequency of LSCs, which is the highest reported to date for precursor T-ALL, and among the highest cancer-initiating cell frequencies reported for any primary malignancy. Our observations for fresh cell transplants are consistent with the proposal that all blasts, or at least a very high proportion, may have leukaemia-initiating potential in some cases of human ALL (Rehe et al, 2013). Furthermore, given that the patient achieved complete morphological and molecular remission with first line chemotherapy and remains in remission 12 months from diagnosis, they also suggest, at least in this case, that existing chemotherapy regimens in ALL successfully target the great majority of cells with leukaemia-initiating potential.…”
Section: Very High Frequencies Of Leukaemia-initiating Cells In Precusupporting
confidence: 90%
“…In precursor B-ALL, NS xenograft-initiating cell frequencies of one in 10 5 -10 7 have been reported (Cobaleda et al, 2000), with higher frequencies observed following intrafemoral transplant into NSG mice (one in 40-10 3 ; le Viseur et al, 2008;Rehe et al, 2013) or where cells from chemorefractory patients are used (one in 10-10 2 ; Morisot et al, 2010). The cellular organization of ALL has variably been argued to be hierarchical (Cobaleda et al, 2000;Cox et al, 2007;Hong et al, 2008) or non-hierarchical (le Viseur et al, 2008Diamanti et al, 2012;Rehe et al, 2013), the latter being based on the identification of LSCs in all of the variable immunophenotypic sub-populations of the disease.…”
Section: Very High Frequencies Of Leukaemia-initiating Cells In Precumentioning
confidence: 99%
See 1 more Smart Citation
“…Rare self-renewing cancer stem cells give rise to more differentiated neoplastic cells with a finite life span, which account for most of the tumor mass, a concept that was also shown to be relevant in leukemic diseases, in particular AML [36]. In contrast, close to 100% of blastic B cells in human B-ALL seem to be capable of initiating the leukemia upon xenotransplantation [37,38]. The leukemia of Kit D814V transgenic mice was successfully transplanted by transfer of low numbers of cells,…”
Section: Discussionmentioning
confidence: 99%
“…The biology of Multiple Myeloma and Pre-B ALL, both B-Cell diseases, has revealed the presence of CD19 in tumor initiating cells [1,2]. Blinatumomab is a bi-specific antibody construct developed with binding domains for both CD19 and CD3 and is approved for relapsed or refractory B-cell ALL with remarkable rates of complete remission in highly refractory cases [3].…”
Section: Introductionmentioning
confidence: 99%